The Dimensionality of Student Engagement and Burnout: A Conceptual and Empirical Extension - Paul Balwant (Journal of Research in Higher Education, 2023)
Student engagement and burnout have received considerable attention from higher education researchers, but there is a dearth of research on the relationships between engagement and burnout dimensions. Accordingly, the present study aims to investigate the relationships between (a) student engagement dimensions, (b) student burnout dimensions, and (c) student engagement and burnout dimensions taken together. A proposed conceptual framework was tested using 207 undergraduate students from British universities. Using structural equation modeling, the findings largely supported the conceptual framework by showing that (a) cognitive engagement is likely to act as a catalyst for emotional and behavioral engagement, (b) exhaustion is likely to precede cynicism, and (c) burnout is likely to result from an erosion of emotional engagement. This study contributes to higher education research by adding to the limited body of work that proposes a more nuanced dimensional perspective on student engagement and burnout research. A limitation and suggestions for future research, as well as practical recommendations, are outlined.